Substitution of 25% of chemical fertilizer nitrogen with organic amendments nitrogen reduces N2O emissions from tea plantation soils in subtropical China - Sun, Qiao; Cheng, Yu; Yin, Suzhen; Sun, Xiaojing; Song, Xiaoyue; Song, Xinyue; Shen, Wanyu; Meng, Biao; Wang, Xinxiao; Lv, Xintong; Li, Hui; Yu, Haiyang (Frontiers in Microbiology, 2025)
Tea plantation soils are recognized hotspots for nitrous oxide (N2O) emissions due to excessive amounts of nitrogen fertilizer applied, yet the potential of partially substituting chemical fertilizers with organic amendments to mitigate this effect remains insufficiently assessed. This study investigated the impact of partial organic substitution on N2O emissions and their underlying mechanisms in a tea plantation soil from southern Anhui, China, by using a 28-day incubation study. Soil samples were subjected to fertilization treatments featuring 25 and 50% substitutions of chemical nitrogen (N) with either pig manure or rice straw. We measured N2O emissions alongside key soil parameters, including soil pH, microbial biomass carbon (MBC), ammonium N (NH4+-N) content, nitrate N (NO3−-N) content, and the abundances of nirS, nirK, and nosZ genes. The results showed that while N application elevated N2O emissions, partial substitution with organic fertilizers effectively mitigated them. Among all treatments, a 25% substitution ratio was optimal, with straw return yielding superior reduction effects compared to pig manure. Structural equation modelling (SEM) revealed that, compared to conventional fertilization, partial replacement of chemical fertilizers with organic amendments elevated soil pH and MBC content, which subsequently mediated the abundances of nirS, nirK, and nosZ genes via the modulation of NH4+-N and NO3−-N content, ultimately leading to reduced N2O emissions. Collectively, these findings indicate that a lower substitution ratio of organic fertilizer can effectively reduce N2O emissions from tea plantation soils, thereby providing a scientific basis for achieving “carbon neutrality” and promoting the sustainable development of tea agroecosystems.